Effect of commercial proteinase inhibitors on the life cycle of the coffee berry borer, Hypothenemus hampei (Ferrari), in artificial diet - RUIZ-SERNA, LORENA; LÓPEZ, JUAN CARLOS; BUSTILLO, ALEX E. (Revista Colombiana de Entomología, 1995)
Three trypsin inhibitors (T9003, T9253, T9378), two Chitinases (C1650, C6137), and a chymotrypsin-trypsin inhibitor (T9777) in two doses (1.0 and 0.1%) were evaluated on a random design with a factorial arrangement of 6x2+2. Each treatment consists of 200 eggs of Hypothenemus hampei. The experimental unit was four eggs placed in 1 cm’ of an artificial diet with 50 repetitions per treatment. The evaluations were made from the eggs hatch until adult emergence (T=28 °C and R.H.= 75%). With the T9003, T9253 and T9378 (1.0 %), the insect life cycle had a mean half-life ± SD) of 20.81 ± 1.64, 21.71 ± 1.93 and 22.57 ± 1.35 days and the mean mortality was 47.69, 57.66 and 60.66%, respectively; for the concentration 0.1% was 21.75 ± 2.11, 23.60 ± 2.59 and 22.23 ± 1.85 days, and the mean mortality was 37.50, 43.0 and 39.33%, respectively. The control allowed the complete life cycle duration, 22.08 ± 1.55 days, and mean mortality of 10.50%. With the chitinases (1.0%), the mean half-life was 20.36 ± 2.51 and 20.37 ± 2.98 days, the mean mortality was 43.25 and 51.40%; for 0.1% the mean half-life was 20.62 ± 2.03 and 20.25 ± 2.33 days, and the mortality was 42.57 and 44.84%, respectively. With the chymotrypsin-trypsin inhibitor in 1.0%, the mean half-life was 20.92 ± 2.44 days and the mean mortality was 33.29%; for 0.1% the mean half-life was 20.89 ± 3.07 days and the mean mortality was 25.61%. The control for the two latter treatments exhibited a complete life cycle duration of 22.21 ± 1.47 days and the mean mortality was 15.43%. In relation to the insect life cycle, there were not significant differences among treatments and the control; in contrast, the mean mortality showed differences, however, this mortality was less than 65%. It is important to continue testing other commercial inhibitors.